Pendampingan Pengurus Dama Dalam Belajar Al-Qur’an di Lingkungan Perumahan Puri Bunga Nirwana Kabupaten Jember - Siti Nursyamsiyah (Mujtama': Jurnal Pengabdian Masyarakat, 2021)
Muslims have the responsibility to learn reciting the holy Koran. This is because fluency in reciting the Koran constitutes a major factor for every Muslim in their daily life. Reciting the Koran constitutes worship and can bestow reward. Allah has rewarded people who recite the Koran. This reward is not only given to those who recite, but also is recommended to those who understand, memorize, listen and practice the meaning in everyday life. Not everyone, however, have the ability to recite the Koran fluently; there are those who are not motivated to learn to read the holy Koran. This mentoring activity, therefore, served as a spirit booster for Dama members and, thus, to provide an example for other housewives living in the Puri Bunga Nirwana housing area.